Prevalence and co-prevalence of comorbidities among patients with type 2 diabetes mellitus living in Puerto Rico - Enid J García-Rivera; Krystel Ruiz-Serrano; Edgar I Miranda; Luis C Mejía; Adolfo Pinzón; Cecile Marqués-Goyco; José G Quijada; Homero Monsanto; Juan C Orengo (Journal of Multimorbidity and Comorbidity)
This is a descriptive study using healthcare claims data from patients with T2DM from public and private healthcare insurance companies providing services in Puerto Rico in 2013, aimed to estimate the prevalence of comorbidities in this population. Descriptive analyses were performed by sociodemographic, and type of service variables using frequency and percent for categorical data or means (+/-SD) or median (IQR) for continuous variables. Chi-square, Fisher exact or two-sample t-tests were used for comparisons. A total of 3,100,636 claims were identified from 485,866 adult patients with T2DM. Patients older than 65 years represented 48% of the study population. Most patients were women (57%) and had private health insurance (77%). The regions of Metro Area (17%) and Caguas (16%) had the higher number of persons living with T2DM. The overall estimated prevalence of T2DM was 17.4%. The number of claims per patient ranged from 1 to 339. A mean of 6.3 claims (SD±9.99) and a median of 3 claims (Q1 1- Q3 8) per subject were identified. Of the 3,100,636 claims most (74%) were related to the diagnosis of diabetes (59%) and associated to outpatient services (88%). The most prevalent comorbidities were hypertension (48%), hyperlipidemia (41%), neuropathy (21%); renal disease (15%), and retinopathy (13%). A high prevalence and co-prevalence of comorbidities and use of healthcare services were identified in patients with T2DM, especially in older adults. Since most comorbidities were due to diabetes-related conditions, this analysis highlights the importance of early diagnosis and adequate management of T2DM patients to avoid preventable burden to the patient and to the healthcare system.